2017
DOI: 10.1177/1010428317705513
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1285-5p influences the proliferation and metastasis of non-small-cell lung carcinoma cells via downregulating CDH1 and Smad4

Abstract: Abnormal expression of microRNAs has been reported to regulate gene expression and cancer cell growth, invasion, and migration. Recently, upregulation of hsa-miR-1285 was demonstrated in bronchoalveolar lavage fluid samples from patients with lung cancer and downregulation in plasma level of stage-I lung cancer patients. However, the function and the underlying mechanism of miR-1285 in non-small-cell lung carcinoma have not been elucidated. In this study, we found that miR-1285-5p, the mature form of miR-1285,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Moreover, hsa_circ_0001206 might function as an miR-1285-5p sponge when exerting its effect on the pathogenesis of PCa. One previous study reported that miR-1285-5p could suppress the proliferation and metastasis of lung cancer cells [35]. Moreover, miR-1285-5p was also reportedly associated with overall survival in breast cancer [36] and infiltrative growth of follicular variants of papillary thyroid carcinomas [37].…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, hsa_circ_0001206 might function as an miR-1285-5p sponge when exerting its effect on the pathogenesis of PCa. One previous study reported that miR-1285-5p could suppress the proliferation and metastasis of lung cancer cells [35]. Moreover, miR-1285-5p was also reportedly associated with overall survival in breast cancer [36] and infiltrative growth of follicular variants of papillary thyroid carcinomas [37].…”
Section: Discussionmentioning
confidence: 95%
“…Zhang et al [21] reported that application of 2 phytotherapeutic agents restored miRNA-331-5p expression and exerted neuroprotective effects by preventing ischaemia-induced inflammasome activation, whereas mi­RNA-331-5p inhibition counteracted these effects. Concerning miR-1285-5p, neonatal and neuroscientific research is scarce, but the literature suggests a role of miRNA-1285-5p in regulation of cell proliferation [22, 23].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…To explore its potential interaction with miRNAs, miR-1285-5p was predicted by homemade microRNA target prediction software from Array star and sooner it was confirmed by dualluciferase. MiR-1285-5p was systematically defined as regulatory factor in tumor progression [83]. Previous reports had indicated that miR-1285-5p could influence the overall survival in breast cancer and infiltrative growth of follicular varients of papillary thyroid carcinomas [84,85].…”
Section: The Epigenetical Roles Of Circular Rnas In Prostate Cancermentioning
confidence: 99%